Comparative Analysis of Time Synchronization Methodologies in Test Range Scenario - Rajak, Chandradeo; Jaiswal, Ankita V; Biswas, Biswajit; Shrivastava, Anupam Kumar (2023 3rd International Conference on Range Technology (ICORT), 2023)
Time synchronization plays a crucial role in scientific study of various events. Most of these experiments need precise time synchronization of various entities up to microseconds or nanoseconds level. This paper presents various methodologies of time synchronization of a sensor instrumentation network in a Test Range where flight trail of Missiles, unmanned aerial vehicles etc. are performed. The time synchronization of tracking sensors is done to precisely time stamp the flight trial data for further analysis and improvement in the system design. Time acquisition using global/regional navigation satellite constellations and its distribution in a large area using legacy serial links, Ethernet network and Fiber Optics will be discussed and compared to achieve these requirements.